A Comprehensive Approach to Posttraumatic Lymphedema Surgical Treatment - Pereira, Nicolás; Oñate, Vanessa; Roa, Ricardo (Archives of Plastic Surgery, 2023)
Background Posttraumatic lymphedema (PTL) is sparsely described in the literature. The aim of this study is to propose a comprehensive approach for prevention and treatment of PTL using lymphovenous anastomosis (LVA) and lymphatic vessels free flap, reporting our experience in the management of early-stage lymphedema.Methods A retrospective observational study was performed between October 2017 and July 2022. Functional assessment with magnetic resonance lymphangiography and indocyanine green lymphography was performed. Patients with lymphedema and functional lymphatic channels were included. Cases with limited soft tissue damage were proposed for LVA, and those with acute or prior soft tissue damage needing skin reconstruction were proposed for superficial circumflex iliac artery perforator lymphatic vessels free flap (SCIP-LV) to treat or prevent lymphedema. Primary and secondary outcomes were limb volume reduction and quality of life (QoL) improvement, respectively. Follow-up was at least 1 year.Results Twenty-eight patients were operated using this approach during the study period. LVA were performed in 12 patients; mean reduction of excess volume (REV) was 58.82% and the improvement in QoL was 49.25%. SCIP-LV was performed in seven patients with no flap failure; mean REV was 58.77% and the improvement QoL was 50.9%. Nine patients with acute injury in lymphatic critical areas were reconstructed with SCIP-LV as a preventive approach and no lymphedema was detected.Conclusion Our comprehensive approach provides an organized way to treat patients with PTL, or at risk of developing it, to have satisfactory results and improve their QoL.
Keywords: lymphedema; posttraumatic lymphedema; SCIP flap; lymphovenous anastomosis; supermicrosurgery